An Analysis of Instructional Facilitators' Relationships with Teachers and Principals. Issue 2 (March 2014) - Range, Bret G.; Pijanowski, John C.; Duncan, Heather; Scherz, Susan; Hvidston, David
This study examines the perspectives of Wyoming instructional facilitators, concerning three coaching constructs—namely, their instructional leadership roles, teachers' instructional practices, and the support that they receive from principals and teachers. Findings suggest that instructional facilitators were positive about their instructional leadership roles and about the support received from principals yet were neutral concerning teachers' autonomy about instructional practices. Instructional facilitators highlighted their roles in mentoring, coaching, and data analysis. Significant differences were found concerning the perceptions of technology instructional facilitators and high school instructional facilitators about their leadership roles, teachers' instructional practice, and support received from principals.